X-RAY IMAGES CONTRAST ENHANCEMENT BASED ON GAMMA CORRECTION - Omarova, Г.; Starovoitov, В. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Due to the nonlinearity of the brightness function created by many medical registration devices, the quality of the medical image deteriorates, which creates problems in the visual research work of doctors. As an example, we can take X-rays. The article studies methods of increasing the contrast of graphic images, in particular methods of improving the quality of X-ray images. The research was carried out in several stages. Attempts were made to increase the contrast of several dozen X-ray images in order to select the best image brightness using the IMADJUST function of the MATLAB system. During the experiments, an increase in contrast was observed, as a result of which a brightness range corresponding to a visual improvement in contrast was selected. The choice of variables γ for the selected range of brightness of the image is made. To obtain the best result, the method of equalizing the histogram of the X-ray image was first used. To quantify the results of the transformation, the niqe and brisque evaluation functions are used, which do not use reference images.